English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-09-02 16:54:35 · 3 answers · asked by goodfatadded 1 in Science & Mathematics Mathematics

3 answers

4th root of xy^3
=(xy^3)^1/4
=x^1/4 y^3/4
This multiplied by xy
=xy(x^1/4 y^3/4)
=x^(1+1/4) y^(1+3/4)
=x^5/4 y^7/4

2007-09-02 17:04:13 · answer #1 · answered by moona 4 · 0 0

You can convert xy to (x^4y^4)^(1/4), and multiply the term in the 4th root directly to get
(x^5y^7)^(1/4)

2007-09-03 00:00:10 · answer #2 · answered by cattbarf 7 · 0 0

x^5/4y^7/4

2007-09-03 00:08:24 · answer #3 · answered by john 4 · 0 0

fedest.com, questions and answers